Studies of Local Lore as a Form of Ethnic Consciousness: The Karelians of Olonets Province in the Nineteenth and Twentieth Centuries - Alexandr M., Pashkov (University of Tartu, Estonian National Museum, Estonian Literary Museum, 2018)
Author deals with 19th century intellectuals of Olonets Karelian origin who started to be interested in local language, culture and ways of life. They started to compile and publish corresponding texts and it meant the beginning of ethnic mobilization of Karelians. Author starts with a brief overview of local historical background and continues with activities of three intellectuals of Karelian origin (I. V. Kondratyev, M. N. Smirnov, N. F. Leskov).